‘If parents are punished for asking their children to feed goats’: supervisory neglect in sub-Saharan Africa - Laird, Siobhan (SAGE, 2016)
Summary: In the United States and the United Kingdom supervisory neglect of children is premised on a construction of childhood which characterises children as essentially vulnerable and in need of constant care and protection by parents. This Western conception has been transmitted to the countries of the sub-Sahara via the Convention on the Rights of the Child. However, the socio-economic and cultural context of African countries differs significantly from those of the United Kingdom and the United States. The incorporation of a Western hegemonic idea of childhood into the national laws of African countries creates fundamental contradictions in the application of criteria for adjudging the adequacy of parental supervision in the sub-Sahara. Drawing on secondary data, this article explores these contradictions and proposes alternative considerations in the conceptualisation and assessment of supervisory neglect. Finding: The combined effects on households in the sub-Sahara of economic conditions, ascribed gender roles and the reciprocal duties held by children to assist their families, contest established indicators and thresholds for supervisory neglect. The concept of societal neglect together with the application of the Haddon Matrix provides a more apposite framework for reducing the risk of significant harm to children. Application: All African countries, excepting Somalia, have introduced the Convention on the Rights of the Child through domestic legislation. The findings of this study are pertinent to policy-makers and social workers in the sub-Sahara. They also invite Western scholars to critically engage with dominant notions of supervisory neglect and re-appraise its applicability in cross-national contexts.